2015
DOI: 10.18052/www.scipress.com/ilshs.61.99
|View full text |Cite
|
Sign up to set email alerts
|

Governance of Citizen Participation and its Related Concepts: A Review of Literature

Michael Li

Abstract: ABSTRACT. This article reviews the concept of citizen participatory governance or citizen participation in public policy-making, a new mode of institutional arrangement increasingly becoming popular in many industrialized democracies. The governance of citizen participation may take different forms, and past studies used different terms in describing the concept. This article take a brief look at various forms of citizen participation (citizen participation in budgeting, collaborative governance, public-privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…A través de esta, se puede medir la calidad de la democracia y la relación Estado -sociedad (Hernández, et al, 2021). De este modo, reforzar la democracia, en el ámbito local, implica, desde el punto de vista político, institucional y administrativo, construir una verdadera cultura política basada en la participación activa de los ciudadanos, que garantice la articulación de espacios ciudadanos de interrelación sociopolítica, a través de mecanismos que promuevan la expresión ciudadana para la definición de políticas, de prácticas y de toma de decisiones sobre asuntos que le afectan (Li, 2015;Hernández, et al, 2021;Fung, 2006;Kelman, Hong y Turbitt, 2013;). Esto es así por cuanto la participación es uno de los elementos esenciales de la cultura política democrática (Peschard, 2001;Hernández, et al, 2021).…”
Section: 2-hacia Una Cultura Basada En La Participación Más Activa De...unclassified
“…A través de esta, se puede medir la calidad de la democracia y la relación Estado -sociedad (Hernández, et al, 2021). De este modo, reforzar la democracia, en el ámbito local, implica, desde el punto de vista político, institucional y administrativo, construir una verdadera cultura política basada en la participación activa de los ciudadanos, que garantice la articulación de espacios ciudadanos de interrelación sociopolítica, a través de mecanismos que promuevan la expresión ciudadana para la definición de políticas, de prácticas y de toma de decisiones sobre asuntos que le afectan (Li, 2015;Hernández, et al, 2021;Fung, 2006;Kelman, Hong y Turbitt, 2013;). Esto es así por cuanto la participación es uno de los elementos esenciales de la cultura política democrática (Peschard, 2001;Hernández, et al, 2021).…”
Section: 2-hacia Una Cultura Basada En La Participación Más Activa De...unclassified
“…With regards to physical activity, previous studies have shown that it contributes to the happiness of older adults and that it directly influences the perceived importance of interpersonal relationships, self-concept, and personal independence (22). On the other hand, an intervention with multicomponent exercise reverts frailty and improves cognitive status, emotional relations, and social networks in weakened older adults (23, 24). In this intervention, the project proposes six areas of intervention through the digital platform: (1) Eat as at home.…”
Section: Description Of the Casementioning
confidence: 99%
“…Citizen participation in policy decision-making is essential for effective governance. It enables governments to make well-informed decisions by incorporating the insights and preferences of the citizens (Li, 2015). This involvement spans various areas, including the public budgeting process, where critical policy and resource allocation decisions are made (Ebdon, 2002).…”
Section: Introductionmentioning
confidence: 99%